The Influence of Measured/simulated Weather Data on Evaluating the Energy Need in Buildings - Ciobanu, Daniela; Eftimie, Elena; Jaliu, Codruta (Elsevier BV, 2014)
In evaluating the thermal energy demand in buildings by using TRNSYS software, weather data are necessary to optimise the implementation location of a new building. The weather data are obtained from in-field measurements, using a weather station, or by using simulated data obtained using the dedicated software, e.g. METEONORM. The paper aims at investigating the influence of measured/simulated meteorological data on an accurate evaluation of the thermal energy demand in buildings. Further on, the paper discusses a case study for a building in Transilvania University of Brasov, located in a mountain, urban area.
Keywords: Weather data; direct solar radiation; space heating demand; METEONORM; TRNSYS